ALANINE AMINOTRANSFERASE/ASPARTATE AMINOTRANSFERASE RATIO REVERSAL AND PROLONGED PROTHROMBIN TIME: A SPECIFIC INDICATOR OF HEPATIC CIRRHOSIS - Siddiqi, Ahmed Imran; Siddiqeh, Musfireh; Mehmood, Asif; Siddiqui, Arif Mahmood (Journal of Ayub Medical College Abbottabad, 2007)
Background: Both ALT/AST ratio reversal (AST/ALT>1) and prolonged prothrombin time are separately related to hepatic cirrhosis. Ratio reversal means that in normal individuals ALT is more than AST and thus ALT/AST> 1 but with development of cirrhosis AST becomes 'º ALT and so AST/ALT>1 or ALT/AST<1. This study was conducted with the idea that prolonged prothrombin time and reversed (AST/ALT >1) ratio together can prove a more specific indicator with a high positive predictive value for the detection of hepatic cirrhosis in patients of chronic liver disease than either of the two alone. Method: This is a comparative cross sectional study. The data of hepatitis B & C patients was collected from the general medical ward and medical out patient department. Clinical and Ultrasonographic features, detected by a single ultrasonologist, were used to diagnose cirrhosis. Patients who were alcoholic were excluded from the study as alcohol itself causes ALT/AST ratio reversal. To avoid laboratory errors and variations the facilities of only a single specific laboratory were used for this study. The sensitivity and specificity of ALT/AST ratio reversal along with positive predictive value were calculated. Then prolonged prothrombin time (PT) and reversed ratio together were used and the results of these two groups were compared. Results: It was found that the reversal of ratio alone is 88% specific as an indicator of hepatic cirrhosis and almost 70% sensitive and have a positive predictive value of 94.5%. The statistical significance test based on z -test for difference of proportion yields: z=6.96 with a p value=0.0000. On the other hand, the prolonged PT and ratio reversal are 98% specific and 53.9% sensitive with a positive predictive value of 98.2%. z -test for difference of proportion yields here: z=6.23 with a p value=0.0000. Conclusion: ALT/AST ratio reversal alone has a high sensitivity and the combined effect of these two parameters increases the specificity as compared to either of the two alone. The high positive predictive value here shows that almost all the patients with reversed ratio and prolonged PT will have cirrhosis. Key Words : ALT/AST ratio reversal, Prolonged PT, Hepatic Cirrhosis.